2008
DOI: 10.1063/1.2834446
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magneto-optical properties of FeRh thin films

Abstract: A systematic investigation of the magneto-optical properties in conjunction with structure and magnetic properties of FeRh thin films epitaxially deposited onto MgO(100) substrates by rf sputter-deposition system was performed. The result, for the first time, shows a (negative) maximum peak of Kerr rotation at around 3.8eV when FeRh thin films are in ferromagnetic state. The polar Kerr rotation angle is found to increase at temperatures above 100°C, which corresponds to the antiferromagnetic-ferromagnetic tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…7 Although the bulk binary system (Fe, Rh) has been extensively studied since the 1940's and rather complete phase diagrams were obtained, work in FeRh thin films has only started relatively recently because of the potential applications in magnetic storage. 6,[8][9][10][11][12][13][14] It was already shown that substitutional doping, 15 magnetic field, 9 strain, 16 film thickness, 11 etc. can be used to modify and tune the magnetic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although the bulk binary system (Fe, Rh) has been extensively studied since the 1940's and rather complete phase diagrams were obtained, work in FeRh thin films has only started relatively recently because of the potential applications in magnetic storage. 6,[8][9][10][11][12][13][14] It was already shown that substitutional doping, 15 magnetic field, 9 strain, 16 film thickness, 11 etc. can be used to modify and tune the magnetic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Research on FeRh was originally conducted on bulk samples [1,[10][11][12] but more recently, due to the envisioned applications [3,5,8], it focuses on thin films. The desired AF phase is present only for a rather narrow interval of the Fe-to-Rh composition ratios [12], which are achieved experimentally by a variation of the deposition conditions [13][14][15] and by a post-preparation heat treatment [16]. Consequently, the growth of high quality FeRh thin films is a rather complex task which requires a lot of optimisation of the preparation procedure and a deposition of large series of samples [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The desired AF phase is present only for a rather narrow interval of the Fe-to-Rh composition ratios [12], which are achieved experimentally by a variation of the deposition conditions [13][14][15] and by a post-preparation heat treatment [16]. Consequently, the growth of high quality FeRh thin films is a rather complex task which requires a lot of optimisation of the preparation procedure and a deposition of large series of samples [13][14][15][16]. The magnetic phase transition in the prepared films is usually studied by magnetometry, for example by superconducting quantum interference device (SQUID), where not only the phase transition temperature but also the remaining uncompensated magnetic moment in the low-temperature AF phase is measured [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre os vários parâmetros importantes se encontra a temperatura à qual é realizado o tratamento térmico posterior à obtenção dos filmes. Nos trabalhos de Inoue et al[30] e Cao et al[31], são feitas comparações entre as características magnéticas e estruturais de filmes finos de composiçãoFe 49 Rh 51 , depositados sobre substratos de MgO (001) e tratados termicamente em temperaturas diferentes. Os filmes foram produzidos via magnetron sputtering em temperatura ambiente, com aproximadamente 150 nm de espessura.…”
unclassified